Effect of Boundary Conditions in Segmental Lining Model on its Sectional Force - S. Chaiyaput; M. Sugimoto (Lowland Technology International, 2016)
Nowadays, underground construction becomes popular as the demand for infrastructure in urban areas increases. To develop underground space in an urban area, it is important to investigate ground surface settlement and damage to existing neighbouring structures. Consequently, 3D finite element method (FEM) continuum models have been developed. This paper introduces a 3D FEM continuum model, which can consider, longitudinal joints, circumferential joints, and nontension boundary between lining and ground, and examines the effect of boundary condition at the tunnel end and ground stiffness on the lining behavior (i.e., bending moment, axial force, normal effective earth pressure, and segment displacement) in the case of staggered building. As a result, it was found that the boundary condition at the tunnel end does not significantly affect the sectional force, except for the axial force in the case of soft soil; The two-ring model provides the safe side results from the viewpoint of segment design; and it can be adopted for segmental lining design and lining behavior simulation.